Technological Knowledge Among Mathematics Pre-Service Teachers in Indonesia and the Philippines: A Comparative Study - Candra Ditasona; Santri Chintia Purba; Stevi Natalia; Hotmaulina Sihotang; Merley Junsay; Rene T Estomo (S&Co Publishing, 2025)
This comparative study investigates the Technological Knowledge (TK) readiness of mathematics pre-service teachers in Indonesia and the Philippines. Using a structured online survey, data were collected from 136 participants in Indonesia and 93 in the Philippines. TK readiness was categorized into three levels: Ready, Moderately Ready, and Not Ready, with demographic factors such as age, sex, and school type examined as potential influences. The results indicate that Indonesian pre-service teachers demonstrate higher TK readiness compared to their Filipino counterparts. No statistically significant associations were found between TK readiness and demographic variables in either country. The findings suggest a need for targeted interventions in teacher education programs to enhance TK competencies and ensure effective technology integration in mathematics classrooms. Implications for curriculum design and future research are discussed.